Unjust enrichment claims & countervailing obligations - Kizhakkevalappil, K (2018)
This thesis investigates the relationship between unjust enrichment claims and countervailing legal entitlements of the defendant. It examines the cases that deny restitution on the basis that the enrichment was owed to the defendant under a valid legal obligation. The authorities suggest that there are two separate rules that perform this function: ‘the good consideration rule’ and the ‘legal obligation qualification’.